2021
DOI: 10.3390/molecules26164935
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Newly Synthesized Benzimidazole and Benzothizole 2,5-Disubstituted Furane Derivatives

Abstract: Newly designed and synthesized cyano, amidino and acrylonitrile 2,5-disubstituted furane derivatives with either benzimidazole/benzothiazole nuclei have been evaluated for antitumor and antimicrobial activity. For potential antitumor activity, the compounds were tested in 2D and 3D cell culture methods on three human lung cancer cell lines, A549, HCC827 and NCI-H358, with MTS cytotoxicity and BrdU proliferation assays in vitro. Compounds 5, 6, 8, 9 and 15 have been proven to be compounds with potential antitum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…SAR study indicated that the placement of isopropylamide ( 107a and 107c ) and 4,5-dihydro-1H-imidazol-2-yl ( 107b and 107d ) moieties at the 5th position of benzothiazole ring improved the antibacterial activity. The existence of nitro ( 107a and 107b ) and chloro ( 107c and 107d ) groups at the para -position of the phenyl ring improved the bacterial inhibition [ 66 ].
Scheme 23 The chemical reaction involved in the preparation of 2,5-disubstituted furan benzothiazole derivatives ( 107a-d )
…”
Section: Other Miscellaneous Benzothiazole Derivatives As Antibacteri...mentioning
confidence: 99%
“…SAR study indicated that the placement of isopropylamide ( 107a and 107c ) and 4,5-dihydro-1H-imidazol-2-yl ( 107b and 107d ) moieties at the 5th position of benzothiazole ring improved the antibacterial activity. The existence of nitro ( 107a and 107b ) and chloro ( 107c and 107d ) groups at the para -position of the phenyl ring improved the bacterial inhibition [ 66 ].
Scheme 23 The chemical reaction involved in the preparation of 2,5-disubstituted furan benzothiazole derivatives ( 107a-d )
…”
Section: Other Miscellaneous Benzothiazole Derivatives As Antibacteri...mentioning
confidence: 99%
“…It has demonstrated efficacy as an antidiabetic, antiulcer, antiinflammatory, anticancer, antiviral, and antimicrobial agent [10]. Numerous studies have underscored the antimicrobial potential of benzimidazole derivatives against various microorganisms [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a focus in this particular discipline involves the creation and development of new anticancer medications with greater cytotoxic efficacy against cancer cells and minimal side effects. Due to their capacity to interact with a variety of different enzymes and receptors, benzimidazoles are well known as biologically significant chromophores in medicinal chemistry (2). Transition metal complexes of such biologically significant ligands exhibit better pharmacological activity than the corresponding free ligand.…”
Section: Introductionmentioning
confidence: 99%